Examining the Relationship Between Social Media Usage, Self-Control, and GPA Among English Education Students at Sriwijaya University - Annisa Aprianti; Alhenri Wijaya (Institut Agama Islam Negeri (IAIN) Curup, 2026)
This study examines social media usage, self-control, and GPA among the English students at Sriwijaya University. The population of this study was 65 English students who enrolled in year 2021 and a purposive sampling was used to select ten participants with moderate to high self-control level. The data were collected, which were then statistically analyzed using Spearman’s rank correlation coefficient and interview was conducted via Zoom Cloud meeting. The result showed that there is no significant correlation between either social media usage or self-control and students’ GPA, which indicates that high social media use is not necessarily associated with lower academic achievement and self-control might have an indirect role in academic success by influencing factors such as time management. Students with moderate to high levels of self-control experienced social media’s negative effect and the enhancement of knowledge when used effectively. They also reported with confidence in maintaining social media use and prioritizing academic responsibilities by regulating strategies such as putting phones away, changing the environment, using phone features, TikTok screen time limit feature, and KiloNotes. The result contribute to discussions about how digital habits and learner characteristics may interact in more nuanced ways, suggesting the need for further research.